The Ingroup–Outgroup Relationship Influences Their Humanity: A Moderation Analysis of Status and Gender - Arriagada-Venegas, Matías; Pérez-Jorge, David; Ariño-Mateo, Eva (Frontiers in Psychology, 2021)
The aim of this study is to examine whether gender and status moderate the teacher–student relationship (TSR) and the perception of dehumanization in teachers and students. A total of 528 participants from a university in Laguna (74% students and 26% professors) completed a questionnaire based on the TSR scale, organizational dehumanization, and demographic variables. PROCESS, a mediation and moderation package, was used to analyze data. The results indicated that ingroup–outgroup relationship significantly influences the perception of organizational dehumanization (p < 0.001). In addition, gender (p < 0.001) and status (p < 0.001) have moderating roles. Specifically, female students are at most risk of perceiving themselves dehumanized, and males with high status (teachers) are less vulnerable to dehumanization. These findings are highly significant for the advancement of knowledge of the intergroup relationship and organizational dehumanization and have practical implications for teachers and students.